Comparison of 3D non-fullerene acceptors for organic photovoltaics based on naphthalene diimide and perylene diimide-substituted 9, 9′-bifluorenylidene. Issue 74 (25th July 2016) - Fan, Yeli; Barlow, Stephen; Zhang, Siyuan; Lin, Baoping; Marder, Seth R.
Abstract : Tetra(PDI) derivatives of non-planar cores have previously been used as acceptors in OPVs; here a tetra(NDI) is shown to be a viable alternative, although, for the pair of acceptors and the donor polymers used here, the PDI species performs better. Abstract : Two non-fullerene acceptors (BF-PDI4 andBF-NDI4 ) have been synthesized by the Suzuki coupling of 2, 2′, 7, 7′-tetrakis(4, 4, 5, 5-tetramethyl-1, 3, 2-dioxaborolan-2-yl)-9, 9′-bifluorenylidene with 1-bromo- N, N ′-di(undecan-6-yl)perylene-3, 4:9, 10-bis(dicarboximide) (PDI-Br) and 1-bromo- N, N ′-dihexylnaphthalene-2, 3:6, 7-bis(dicarboximide) (NDI-Br), respectively. The photovoltaic performance ofBF-PDI4 andBF-NDI4 as acceptors was investigated by fabricating inverted solar cells with structure: ITO/ZnO/active layer/MoO3 /Ag. Power-conversion efficiencies of 3.64% and 2.28% were achieved usingBF-PDI4 andBF-NDI4 respectively as the acceptor in a blend with the polymer PTB7-Th as a donor. AlthoughBF-PDI4 exhibits much stronger visible absorption than its NDI analogue this absorption makes a relatively small contribution to the photocurrent; however, the photocurrent resulting from polymer absorption in theBF-PDI4 films is larger than that inBF-NDI4 -based cells.